Data for: Uniform 182W isotope compositions in Eoarchean rocks from the Isua region, SW Greenland: the role of early silicate differentiation and missing late veneer ... - Tusch, Jonas (Mendeley, 2020)
research data for the manuscript: Uniform 182W isotope compositions in Eoarchean rocks from the Isua region, SW Greenland: the role of early silicate differentiation and missing late veneer ...